Citrullus vulgaris المعزولين من نبات الرقي Rhizoctonia solani و Fusarium oxysporum في نمو الفطرين Capparis spinosa (تأثير مستخلصات أوراق نبات الشفلح (الكبر - هاشم ياسرمحمد (University of Thi-Qar Journal of Science, 2019)
This study was conducted during the period from the beginning of September to the end of October 2009, to study the effect of leaf extracts capers against F. oxysporum and R. solani which were isolated from infected plants by the vascular wilt , the survey show that plant extracts contain the active substances of plant extracts , Alkaloids , Saponins , Tannins , Phenplic compound , Resins , Terpins. It was found that water extracts had inhibited the growth of R. solani 100% in 20 and 40 mg/ml of cold water extraction and in all concentrations for hot water extraction and concentration of 40 mg/ml when the treated by phenolic extract . The effectiveness of the extracts in F. oxysporum was tested .It was the percentage of inhibition was 100% in 20 and 40 mg/ml when the treated by hot water extract , reaching 100% in 40 mg/ml when treated by cold water extracts , Other extracts inhibition ratios ranged between (26.5-88.3)% at different concentrations. A Soil test was conducted to determine the ability of water extracts to protect seedlings of the plant progress where plant extracts showed good protection by measuring plant lengths with no symptoms of withering plants when compared with pesticide Benomyl and infection control